Gandhiji’s Journalism and the Indian National Movement: गांधीजी की पत्रकारिता और भारतीय राष्ट्रीय आंदोलन - Choudhary, Vasu; Shahu, Geeta (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Mahatma Gandhi was a great leader of the Indian freedom struggle. He left a unique mark on pre-independence Indian politics, social reform, economic self-reliance, and particularly journalism. Gandhiji used journalism as a powerful medium to awaken public consciousness and transform the freedom struggle into a mass movement. A firm believer in truth and non-violence, he advocated their practice in every sphere of life. During the national movement, various nationalist forces worked in their own ways for the country’s liberation, with the common goal of freeing India from imperialist rule. Lawyers and renowned journalists were especially active in the movement. Although Gandhiji never considered himself a journalist, he became widely recognized as one, owing to his role in awakening the masses to their national duty. Objective: This research paper analyzes the role of Gandhiji’s journalism in the context of the Indian National Movement. Abstract in Hindi Language: महात्मा गांधी भारतीय स्वतंत्रता संग्राम के एक महानायक थे। उन्होंने भारतीय राष्ट्रीय आन्दोलन स्वाधीनता पूर्व भारतीय राजनीति, समाज-सुधार, आर्थिक स्वराज, आत्मनिर्भरता और पत्रकारिता जैसे क्षेत्रों में अपना अद्वितीय प्रभाव स्थापित किया। गांधी जी ने पत्रकारिता को एक सशक्त माध्यम के रूप में प्रयोग किया, जिससे उन्होंने जनमानस को जागरूक किया और स्वतंत्रता संग्राम को व्यापक जन-आंदोलन का रूप दे दिया। गांधी जी सत्य और अहिंसा के आग्रही थे, वह चाहते थे कि इस सत्य और अहिंसा का पालन जीवन के सभी क्षेत्रों में होना चाहिए। भारतीय राष्ट्रीय आन्दोलन में सभी राष्ट्रवादी शक्तियां अपने अपने ढंग से राष्ट्र की मुक्ति के लिए कार्यरत थीं। साम्राज्यवादी सत्ता से भारत की मुक्ति ही सबका उद्देश्य था। भारतीय राष्ट्रीय आन्दोलन में अधिवक्ता और ख्याति प्राप्त पत्रकार अतिशय सक्रिय थे। यद्यपि गांधीजी अपने को कभी पत्रकार नहीं माने। वह जनसमुदाय को राष्ट्र के प्रति जागृत करने के लिए पत्रकार के रूप में भी ख्यातिलब्द्ध हैं। उद्देश्य- प्रस्तुत शोध-पत्र गांधीजी की पत्रकारिता की भूमिका को राष्ट्रीय आंदोलन के संदर्भ में विश्लेषित करता है। Keywords: राष्ट्रीय आन्दोलन, पत्रकारिता, निष्पक्षता